Interactive computer graphics a top-down approach using OpenGL - Angel, Edward (Pearson/Addison-Wesley, 2009)
This fifth edition of Edward Angel's 'Interactive Computer Graphics' again introduces topics in its trademark top-down, programming-oriented approach. The aim is that students will quickly be able to create exciting interactive graphics applications using Open GL.